The role of peer tutoring and authentic assessment in developing junior high school students’ English-speaking skills - Fairus Sintawati; Asih Rosnaningsih (Universitas Muhammadiyah Malang, 2026)
The primary issue in this study is junior high school students’ low English-speaking skills, which are brought on by a lack of vocabulary, communication anxiety, and conventional teacher-centered learning methods that only concentrate on grammar. This study investigated into how students' speaking skills was influenced by combining peer tutoring and authentic assessment techniques. In order to get a comprehensive picture of effectiveness, a mixed method was employed, which blends qualitative and quantitative methodologies using correlational study. As many of 178 students of seventh graders of Junior High School in Serang District as the research population with sample of 69 students (grades VII-A and VII-C) was chosen by simple random sampling. A Questionnaires, interviews, observations, and speaking performance evaluation rubrics with both linguistic and non-linguistic components were used as data gathering tools. The research results show that the integration of peer tutoring and authentic assessment has a positive and significant effect on students' speaking skills (F-count= 35.953; Sig.<0.05) with an R Square value of 0.521 or 52.1%. The implications of this research provide pedagogical alternatives for teachers to create participatory, communicative, and student-centered learning to prepare practical competencies in the real world.